"Data is [G]od": The influence of cumulative policy reforms on teachers' knowledge in an urban middle school in the United States. (July 2020) - Craig, Cheryl J.
Abstract: This narrative inquiry centers on teachers' longitudinal experiences of policy-related reforms systematically introduced to T. P. Yaeger Middle School, a campus located in the fourth largest, second most diverse city in America. The embedded research study, with roots tracing back to 1997, uses five interpretive tools to capture six mandated changes in the form of a story serial. Special research attention is afforded pay-for-performance, the sixth reform in the series. The deeply lived consequence of receiving bonuses for his teaching performance prompted Daryl Wilson, Yaeger's long-term literacy department chair, to proclaim "data is [G]od." Wilson's emergent, inventive metaphor aptly portrays the perplexing conditions under which his career ended, and how my long-term research project likewise concluded. Highlights: Six policy-related reforms having to do with standardization were introduced to one American middle school over two decades. The teachers intuitively created metaphors to convey their policy-related reform experiences. The metaphors served as "containers" for "compressed narratives". The six metaphors ran against the grain of the image of teachers-as-curriculum makers. The metaphor, "data as [G]od, " particularly took its toll on the teachers.